2018
DOI: 10.1093/molbev/msy002
|View full text |Cite|
|
Sign up to set email alerts
|

Deuterostome Genomics: Lineage-Specific Protein Expansions That Enabled Chordate Muscle Evolution

Abstract: Fish-like larvae were foundational to the chordate body plan, given the basal placement of free-living lancelets. That body plan probably made it possible for chordate ancestors to swim by beating a tail formed of notochord and bilateral paraxial muscles. In order to investigate the molecular genetic basis of the origin and evolution of paraxial muscle, we deduced the evolutionary histories of 16 contractile protein genes from paraxial muscle, based on genomic data from all five deuterostome lineages, using a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 55 publications
1
15
0
Order By: Relevance
“…2015), but it also identified those that contributed to formation of chordate characteristics (Inoue et al. 2017; Inoue and Satoh 2018).…”
Section: Introductionmentioning
confidence: 99%
“…2015), but it also identified those that contributed to formation of chordate characteristics (Inoue et al. 2017; Inoue and Satoh 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Third, smooth muscles are also thought to be absent from tunicates [ 14 , 97 ], the sister group to the vertebrates within the phylum Chordata [ 24 ]. Although tunicate adult body wall muscles are structurally non-striated, they use conventional striated muscle contractility effectors and are specified by MRF, suggesting they have secondarily lost their striations [ 51 , 80 ]. Recent studies have revealed that tunicates possess homologs of various structures, cell types, and tissues that were previously presented as vertebrate novelties [ 1 , 2 , 27 , 98 , 100 ].…”
Section: Introductionmentioning
confidence: 99%
“…The mid‐dorsal fold gives rise to notochord, and the left and right folds form somites in neurulae. In addition, cephalochordate notochord is composed of myofibrils, like the somites on both sides (Inoue & Satoh, ; Ruppert, ; Suzuki & Satoh, ). On the other hand, urochordate and vertebrate embryos form the notochord by convergent extension of its presumptive cells, which occur on both sides of early‐stage embryos (Satoh, ).…”
Section: Introductionmentioning
confidence: 99%